Development of images to braille conversion software for symbols using template matching with rules base (images to editable text for debraillso) - Mohd Solahuddin, Jaafar (2011)
The blind people who need to read text always face some problems because they only can read Braille dots.The reading materials for them are very limited as they are unable to read available normal reading materials.Images to Braille conversation Software/hardware(Symbols)is a system that helps Blind people to read available reading materials.The current system only can support upper-case English alphabets from A to Z using six dots.Hence,to complete the current system,we have developed a complete images to Braille conversation system to process and convert the images of normal texts into Braille dots (8 dots) taking into account(i)lower/upper case English alphabets,(ii) numbers and(iii)special characters/symbols all together. Particularly,this research focuses on the part two, which is the processing and conversion of special characters/symbols. The special characters such as (" - = [].Need special treatment to convert it to Braille.This system is able to convert any scanned, captured or saved image of symbol's into Braille.This system receives the input images, process and compares it with characters templates that have been stored in the database.The processing of image is done into five steps systematically as:(i)binarization and pixel inversion,(ii) noise removal,(iii)segmentation and clustering,(iv)line identification and finally(v)character extraction.A GUT is developed to observe the processed and displayed Braille dots to ensure the accuracy.Followed by a hardware is developed to demonstrate the working ability to display the Braille dots in terms Led.The Blind people only need to capture the text picture using a hardware tool such as camera to get digital image and fed into the system,then the system will convert and display the Braille dot automatically.(This system is targeted to integrate with Alphabets and Numbers and then use with hand phone or camera as a handy plug-in/plug-out device.)So that the blind people can carry it anywhere any time with them to capture picture and make it readable for them.They also will be able to read the received SMS in their hand phone.The system also will read the material aloud for additional convenience for this group of people so that they can read and listen as per need.The developed integrated system may offer an easy life for the Blind community by widening the reading materials in a affordable and convenient way.